Growth of carbon nanotubes on carbon fiber at relatively low temperature for improved interfacial adhesion with epoxy - Yao, Zhiqiang; Wang, Chengguo; Wang, Yanxiang; Qin, Jianjie; Wang, Qifen; Wei, Huazhen (Journal of materials science, 2022)
In order to improve the interfacial adhesion of epoxy composites, a hierarchical structure including carbon nanotubes (CNTs) grown on carbon fiber (CF) was prepared by a novel vacuum-assisted chemical vapor deposition (CVD) method at relatively low temperature of 400 °C under a pressure of 0.01 MPa. The short beam method and microbond test were used to measure the interlaminar shear strength (ILSS) and interfacial shear strength (IFSS) of epoxy composites reinforced by different CFs. The results showed that the CNTs-grown CF prepared at the H 2 flow rate of 9 L/min had the best reinforcement effect. The ILSS and IFSS of its composites were 19.50% and 62.32% higher than that of the CF/epoxy composites without CNTs grown, respectively. The improvement of interfacial adhesion can be attributed to the fact that CNTs inserted into the matrix enhanced the mechanical interlocking between the fiber and the resin and induced the formation of interphase. Also, two failure modes of CNTs have also been observed, which can absorb extra energy and increased the difficulty of the separation of fiber and resin. The increase in the glass transition temperature ( T g ) indicated the movement of the polymer molecular chains at the interphase was restricted by CNTs, which also contributed to the improvement of the interfacial adhesion of composites.